Heart rate variability and plasma biomarkers in patients with type 1 diabetes mellitus: Effect of a bout of aerobic exercise - Anaruma, Chadi P. [UNESP]; Ferreira, Maycon [UNESP]; Sponton, Carlos H.G. [UNESP]; Delbin, Maria A.; Zanesco, Angelina [UNESP] (Elsevier, 2016)
Objective: The aim of this study was to evaluate: (1) the cardiovascular parameters and plasma biomarkers in people with type 1 diabetes mellitus (T1DM) at baseline; and (2) the heart rate variability (HRV) and blood glucose in response to a session of aerobic exercise (AE) and during recovery period. Research design and methods: Adults (18-35 years) were divided into two groups: control (CT, n = 10) and T1DM (n = 9). Anthropometric, cardiovascular, and biochemical parameters, and aerobic capacity (indirect peak oxygen uptake, VO2peak) were evaluated at baseline. Thirty minutes of AE (40-60% intensity) was performed on a treadmill. Blood glucose and HRV were determined at rest, during AE, and during the recovery period. Results: Anthropometric measurements, cardiovascular parameters, aerobic capacity, and biochemical parameters were similar between the groups at baseline. In the T1DM group, blood glucose, glycated hemoglobin, and thiobarbituric acid reactive substances concentrations were increased while nitrite/nitrate (NOx -) levels were reduced. During AE, the magnitude of the reduction of blood glucose was greater than that during the recovery period in the T1DM group. The RR intervals and SDNN were reduced at rest as well as in the recovery period in T1DM subjects, whereas the RMSSD and pNN50 were only reduced during the recovery period. No changes were observed in low frequency (LF), high frequency (HF), and LF/HF ratio. Conclusion: Our study shows that T1DM patients on insulin therapy have poor blood glucose control with greater lipid peroxidation and lower NOx - levels, accompanied by an imbalance in autonomic function detected by the challenge of AE.
Keywords: Acute aerobic exercise; Blood glucose; Heart rate variability; NOx -; Thiobarbituric acid reactive substances (TBARS); Type 1 diabetes mellitus